Xenopus Oocyte As a Model System to Study Store-Operated Ca2+ Entry (SOCE) - Courjaret, Raphaël; Machaca, Khaled (Frontiers in Cell and Developmental Biology, 2016)
Store-operated Ca2+ entry (SOCE) is a ubiquitous Ca2+ influx pathway at the cell membrane that is regulated by Ca2+ content in intracellular stores. SOCE is important for a multitude of physiological processes, including muscle development, T-cell activation and fertilization. Therefore understanding the molecular regulation of SOCE is imperative. SOCE activation requires conformational and spatial changes in proteins located in both the endoplasmic reticulum and plasma membrane. This leads to the generation of an ionic current of very small amplitude. Both biochemical and electrophysiological parameters of SOCE can be difficult to record in small mammalian cells. In this protocol we present the different methodologies that enable the study of SOCE in a unique model system, the frog oocyte, which provides several advantages and have contributed significantly to our understanding of SOCE regulation.